Companies, creation and development of Dosquebradas (2019)
In this document are studied the two moments which can be identified clearly.Dosquebradas lived a process of land occupation in two clearly identifiedmoments: one of them, for being a proximity to the Development Pole that wasPereira of the 30s and 40s (city that has historically been linked); the other one,moved by the settlement of foreign and nationals companies on its territory.Despite its unparalleled perspectives of development and economic growth,the ones with the municipality was born, these became diluted over time, soeconomic interests of businessmen and politicking prevailed in the territoryeven before becoming town, resulting in its staggering economic growth, butwith serious flaws in their social development